Prevalence of Sarcopenia and Its Effect on Postoperative Complications in Patients with Crohn’s Disease - Chen Zhang; Dingye Yu; Liwen Hong; Tianyu Zhang; Hua Liu; Rong Fan; Lei Wang; Jie Zhong; Zhengting Wang (Gastroenterology Research and Practice)
Background and Aims. Sarcopenia is a prognostic factor of outcomes for various diseases, but reports on sarcopenia in patients with Crohn’s disease (CD) are few. We aim to determine the prevalence of sarcopenia and assess the role of sarcopenia in postoperative complications in patients with CD at a tertiary referral center. Methods. Patients who underwent intestinal surgery for CD from January 2013 to October 2019 were retrospectively enrolled. The L3 skeletal muscle mass index (SMI) was used to identify sarcopenia. Demographic data, preoperative laboratory data, surgical details, and hospital outcomes were recorded. The factors associated with postoperative complications were evaluated through univariate and multivariate analyses. Results. One hundred and twenty-four patients were enrolled. Thirty-four of them (27.4%), including 11 males, were diagnosed with sarcopenia. Compared with patients without sarcopenia, sarcopenic patients had a significantly lower BMI (P<0.001); lower preoperative serum albumin (P=0.006), prealbumin (P=0.030), and hemoglobin levels (P<0.001); longer hospital stay (34.4±26.8 days vs. 22.8±15.6 days, P=0.003); and more occurrences of complications (41.2% vs. 23.3%, P=0.049). The overall incidence of postoperative complications was 28.2%. Infection (51.4%) and intestinal fistula (22.9%) were the most common among such complications. Through the multivariate analysis, sarcopenia was identified as an independent risk factor for major postoperative complications (odds ratio=3.974, 95%CI=1.171–13.489, P=0.027). Conclusion. Sarcopenia is common in patients with CD requiring bowel resection, and it significantly increases the risk of major postoperative complications.